THE STRUCTURE CONTROL OF THE LARGE DIMENTION CASTINGS OF HIGH-TESTED CAST-IRON WITH THE HELP OF APPARATUS “SORTER MAGNETIC MS-1” - S. G. Sandomirskij (Литьë и металлургия, 2004)
The physical principles of magnetic grading of the high-test cast iron castings by structure are analyzed. It is informed about the developed apparatus “Magnetic sorter M C-1”, based on the method ''point pole”. There are given the examples of using of the apparatus at the enterprises of Belarus for control of the structure of the large dimension castings of high-strength cast iron.